Evaluation of Glucose Uptake in Normal and Cancer Cell Lines by Positron Emission Tomography - Francesca Maddalena; Giacomo Lettini; Rosj Gallicchio; Lorenza Sisinni; Vittorio Simeon; Anna Nardelli; Angela Assunta Venetucci; Giovanni Storto; Matteo Landriscina (Molecular Imaging)
To date, there is no definitive demonstration of the utility of positron emission tomography (PET) in studying glucose metabolism in cultured cell lines. Thus, this study was designed to compare PET to more standardized methods for the quantitative assessment of glucose uptake in nontransformed and transformed living cells and to validate PET for metabolic studies in vitro. Human colon and breast carcinoma cell lines and mouse embryo fibroblasts were evaluated for [ 18 F]fluorodeoxyglucose ([ 18 F]FDG) uptake by PET and autoradiography and 2-deoxyglucose (2-DG) incorporation by colorimetric assay and analyzed for the radiotoxic effects of [ 18 F]FDG and the expression levels of glucose transporters. Indeed, [ 18 F]FDG incorporation on PET was comparable to [ 18 F]FDG uptake by autoradiography and 2-DG incorporation by colorimetric assay, although radiotracer-based methods exhibited more pronounced differences between individual cell lines. As expected, these data correlated with glucose transporters 1 to 4 and hexokinase II expression in tumor cell lines and mouse fibroblasts. Notably, [ 18 F]FDG incorporation resulted in low apoptotic rates, with fibroblasts being slightly more sensitive to radiotracer-induced cell death. The quantitative analysis of [ 18 F]FDG uptake in living cells by PET represents a valuable and reproducible method to study tumor cell metabolism in vitro, being representative of the differences in the molecular profile of normal and tumor cell lines.